Trabalhando a notícia em sala de aula - Silva, Paula Márcia Lázaro da (2015)
The teaching of Portuguese language presents itself as a challenge for teachers, especially regarding the presentation of relevant proposals for the construction of knowledge of the language, since it is increasing the number of students who have difficulties in the interpretation and production of texts. In this context, the didactic sequences appear to help the teacher as facilitator language teaching through genres, providing actions that prioritize the construction of knowledge and the appropriation of language, based on previous knowledge of students. Our goal in this research is to discuss the teaching of Portuguese language through genres, using the didactic sequence procedure, noting its advantages and contributions in teaching mother tongue and its use by teachers. We based our study in the guidelines of the National Curricular Parameters for Portuguese Language (BRAZIL, 1998), in Bakhtin\'s conception of discourse genres (Bakhtin, 2011). The adoption of this proposal to work with the news genre seeks to develop discursive competence and encourage the effective participation of students in society through the conscious use of language in social practices of reading and writing. The methodology of action research was used for this work, whose practical goal was achieved in the development of a didactic sequence to work with gender, as advocated Dolz, Noverraz and Schneuwly (2004). The main results show us that the sequenced activities are an important tool at work genres because they work according to the actual needs of the class.